The Role of Government Internal Supervisory Apparatus (APIP) in Corruption Prevention in Local Governments Districts/Cities Central Sulawesi Province - OSTENSIO, Gracelia N.; DIN, Muhammad; MASRUDDIN, Masruddin; TANRA, Andi Ainil Mufidah (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the role of Government Internal Supervisory Apparatus, which consists of three indicators—APIP Capability, SPIP Maturity, and TLRHP in the corruption prevention across 13 districts/cities governments in Central Sulawesi Province. Data analysis was conducted using WarpPLS 7.0 software to assess the effect of each variable on corruption prevention. The results of the study indicate that all three indicators have a significant influence on enhancing corruption prevention efforts. APIP plays a major role and holds significant responsibility in realizing accountable and transparent financial governance in government. In this regard, APIP serves as a bridge between the government and the public to build public trust in government institutions through proactive prevention efforts. The role of APIP is crucial in creating an environment that supports corruption prevention; therefore, commitment and consistency from local governments are required to improve APIP capabilities, SPIP maturity, and follow-up on Audit Board of Indonesia (BPK) recommendations.